How and what we eat impact our environment - Rafael de Freitas Juliano; Jonathan Ballico de Moraes (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2021)
Our dietary choices are one of the leading global causes of environmental degradation and decline in human health. The increasing consumption of fossil fuels, the emission of greenhouse gasses, deforestation and the extraction of fresh water by the food industry have triggered worldwide concern about the western lifestyle and our future in this world. Although modernization and new technologies in agriculture have helped end hunger, the lack of communication with environmental development promotes water and consequently food insecurity around the world, as well as malnutrition and an increase in chronic diseases. This mini-review summarizes the environmental and health impacts caused by the Western food industry and shows that we need to promote the development of food science together and in a communicative way with health and environmental sciences.